2009
DOI: 10.1017/s1366728909990447
|View full text |Cite
|
Sign up to set email alerts
|

Child L2 development of syntactic and discourse properties of Spanish subjects

Abstract: The apparent optionality in the use of null and overt pronominal subjects and the apparently free word order or distribution of preverbal and postverbal subjects in Spanish obey a number of discourse-pragmatic constraints which play an important role in Spanish L2 subject development. Although research on subject properties at the syntax-discourse interface has been conducted in adult L2A and bilingual L1A, child L2A has not been extensively explored in this respect. This paper explores the L2 development of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Yet this occurs much later than in L1A, given that we are obviously dealing with a different process of acquisition in L2A, which is mainly affected by the children’s L1 and other external factors inevitably leading to lack of uniformity and slower rate of acquisition. Interestingly enough, in her study of child L2A acquisition of Spanish subject properties, Pladevall Ballester (2010) found that L1 English 5-year-old children acquiring L2 Spanish found it hard to correctly judge null/overt subjects in subordinate clauses in L2 Spanish and obtained much more accurate results in judging null/overt subjects in root positions. 8 In order to test whether the differences between L1 and L2 children are due to L1 Transfer or developmental effects a comparison between L2 English children from a null subject L1 language and a non-null subject L1 language would have to be made, which is beyond the aims of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet this occurs much later than in L1A, given that we are obviously dealing with a different process of acquisition in L2A, which is mainly affected by the children’s L1 and other external factors inevitably leading to lack of uniformity and slower rate of acquisition. Interestingly enough, in her study of child L2A acquisition of Spanish subject properties, Pladevall Ballester (2010) found that L1 English 5-year-old children acquiring L2 Spanish found it hard to correctly judge null/overt subjects in subordinate clauses in L2 Spanish and obtained much more accurate results in judging null/overt subjects in root positions. 8 In order to test whether the differences between L1 and L2 children are due to L1 Transfer or developmental effects a comparison between L2 English children from a null subject L1 language and a non-null subject L1 language would have to be made, which is beyond the aims of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The study of child L2A is now a focus of research, particularly regarding its similarities and differences in different grammatical areas with respect to child L1A and adult L2A (Blom, 2008; Ionin, 2008; Meisel, 2007; 2008, 2009; Pladevall-Ballester, 2010; Schwartz, 2004; Unsworth, 2005b; Whong-Barr and Schwartz, 2002, among others). Child L2A shares representational and developmental properties of both L1A and adult L2A and hence it is a valuable tool in the general picture of language acquisition (Lakshmanan, 1995; Schwartz, 1992, 2003, 2004).…”
Section: The Importance Of Child L2amentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption has resulted in the exploration of how syntactic and morphological features are related to the organization of the lexicon, how functional features are linked to lexical items (Chomsky 1995;Jackendoff 2002), and how functional features/values are mapped onto morphology and/or intonational patterns (Cheng and Rooryck 2000;McFadden 2004;Adger and Svenonius 2011) and to informational structure (Adger 2003;Cinque 1999;Rizzi 1997). In studies of simultaneous, early, and late bilingualism, the focus on interfaces has provided evidence of cross-linguistic influence at the interfaces between the computational system and other components such as pragmatics, semantics, and phonological form (PF) (Hulk and Müller 2000;Montrul 2010;Sorace 2011;White 2011;Pladevall 2010;Serratrice et al 2004;Sorace and Serratrice 2009;inter alia). Evidence of crosslinguistic influence has also been found at the lexical-functional interface (Liceras et al 2005;Fuertes and Liceras 2010;Austin 2009;Liceras et al 2008;Cuza et al 2013;Bruhn de Garavito and Valenzuela 2008;Montrul 2009; inter alia), and at the semantics/morphology interface (Slabakova 2008).…”
mentioning
confidence: 99%
“…It has also been attested among aphasics and in first-language acquisition, although transitorily in the case of the latter (for discussion, see, for example, Avrutin, 2004). In recent years, researchers in multilingualism have taken a particular interest in optionality, noting its presence among child second-language (L2) acquirers (Pladevall Ballester, 2010), adult L2 acquirers (Sorace, 1999, 2000a; White, 1992), and among bilingual Heritage Speakers in the United States (de Prada Pérez and Pascual y Cabo, 2012; Silva-Corvalán, 1994). It also forms a crucial part of the Interface Hypothesis (IH, e.g.…”
Section: Introductionmentioning
confidence: 99%